Visual Aspects of Scribal Culture in Ashkenaz Shaping the 'Small Book of Commandments' (SeMaK) - Kaufmann, Ingrid M. (Studia Judaica, 2019)
The medieval Ashkenazi manuscripts of the Small Book of Commandments (Sefer Mitzvot Katan, or ‘SeMaK’ for short), which was written by Isaac of Corbeil, attest a scribal culture in which rabbinical knowledge and piety were combined with creative freedom in manuscript design. This study is concerned with the creation, composition and circulation of manuscripts of the SeMaK and concentrates on the book as an artefact. The focus of the author’s attention is the manuscripts’ material nature, their artistic embellishment and the personal touches that scribes added to them. With the act of writing a text and decorating a SeMaK manuscript, they ‘appropriated’ the text, so to speak, giving it a character of its very own. They drew on a visual language in the process – or rather, on visual languages, which occupy a special place between pure writing culture and pure painting culture. It was in this area ‘in between’ the two that spontaneous touches arose, ranging from changes in the physical arrangement of the text (mise-en-page) to drawings and doodles added in the margins. An examination of paratextual elements broadens the reader’s knowledge about Jewish scribal culture and grants insights into medieval book art, material culture and Judeo-Christian co-existence in the Middle Ages as well as throwing some light on Jewish values, ideals and eschatological hopes